A Low-Complexity Control for Nonlinear Vehicular Platoon with Asymmetric Actuator Saturation - Guo, Xianggui; Wang, Jianliang; Liao, Fang; Xiao, Wendong; Li, Hongjian (IEEE International Conference on Control and Automation (Print), 2018)
An approximation-free adaptive PID-based sliding mode control (PIDSMC) scheme is designed for nonlinear vehicle platoon subject to asymmetric actuator saturation, capable of guaranteeing, for any initial system condition, string stability of the whole vehicular platoon. It is shown that under the proposed scheme, the whole vehicle platoon can tolerate the asymmetric actuator saturation and unmodeled dynamic nonlinearities, and the scheme also retains the main advantages of the PIDSMC technique. These advantages include robustness and capability to reduce the spacing errors and chattering and to eliminate the steady-state spacing errors. Moreover, adaptive compensation instead of approximation approach such as neuro-network and fuzzy logic approaches is adopted to attenuate the negative effects caused by asymmetric actuator saturation and unmodeled dynamic nonlinearities. Furthermore, constant time headway is used to achieve the string stability and simultaneously to increase traffic density and address the negative effect of nonzero initial spacing, velocity and acceleration errors. Compared with most existing methods, the proposed method does not linearize the system model and neither requires precise knowledge of the system model. Finally, a numerical example is proposed to show the effectiveness of the proposed scheme.